2021
DOI: 10.3389/fmicb.2021.678323
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Autotrophic Denitrifiers From Anaerobic Sludge Using Sulfurous Electron Donors

Abstract: Graphical Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 73 publications
(98 reference statements)
2
13
0
Order By: Relevance
“…Denitrification in UASB sludge and the influence of microbial community were also studied by Carboni et al [ 105 ]. Adding electron donors (such as sulfur, pyrite, thiosulfate, and sulfide), the microbial community diversity significantly reduced and only several genera of autotrophic denitrifiers (such as Thiobacillus , Thioprofundum , and Ignavibacterium ) were selected and therefore becoming dominant as reported by [ 105 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Denitrification in UASB sludge and the influence of microbial community were also studied by Carboni et al [ 105 ]. Adding electron donors (such as sulfur, pyrite, thiosulfate, and sulfide), the microbial community diversity significantly reduced and only several genera of autotrophic denitrifiers (such as Thiobacillus , Thioprofundum , and Ignavibacterium ) were selected and therefore becoming dominant as reported by [ 105 ].…”
Section: Resultsmentioning
confidence: 99%
“…Denitrification in UASB sludge and the influence of microbial community were also studied by Carboni et al [ 105 ]. Adding electron donors (such as sulfur, pyrite, thiosulfate, and sulfide), the microbial community diversity significantly reduced and only several genera of autotrophic denitrifiers (such as Thiobacillus , Thioprofundum , and Ignavibacterium ) were selected and therefore becoming dominant as reported by [ 105 ]. Zhang et al [ 106 ] found that mixotrophic conditions can inhibit the denitrification in the anammox system but at the same time can enhance the ability of Candidatus Kuenenia to use diverse types of carbon sources.…”
Section: Resultsmentioning
confidence: 99%
“…Sulfur (SR) and pyrite (PR) fluidized bed reactors were respectively inoculated with sulfur and pyrite oxidizing denitrifying cultures, which were enriched as described previously (Carboni et al, 2021). Sterile anoxic basal medium used during the enrichment process was prepared as described by Stams et al (1993) comprising of (g/L): 1.2 KNO 3 ; 0.41…”
Section: Source Of Biomass and Media Compositionmentioning
confidence: 99%
“…This behavior makes them suitable, slow-release electron donors for autotrophic denitrification. Preliminary experiments with pyrite showed several advantages such as the preservation of a stable pH without the addition of any base addition (Hu et al, 2020) and low sulfate production (Di Capua et al, 2020;Carboni et al, 2021), however its application might lead to lower nitrogen removal rates compared with S 0 -driven denitrification (Liu et al, 2021). Therefore, further studies on pyritedriven autotrophic denitrification are of great interest, mainly aiming at increasing denitrification rates in continuous-flow bioreactors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation